Alloying strategy for constructing multi-component nano-catalysts towards efficient and durable oxygen evolution in alkaline electrolyte. (20th September 2021) - Jiang, Shunda; Duan, ChanQin; Li, Xinglong; Wang, Dan; Wang, Zhiyuan; Sun, Hongyu; Zheng, Runguo; Liu, Yanguo
Highlights: A series of copper-based alloys are prepared by microwave-assisted polyol method. FeCoCu and FeCoNiCu exhibit the excellent OER catalytic activity and stability. Multi-metal synergy improves the catalytic performance of copper-based alloys. Introducing FeCoNi into Cu can accelerate electron transfer and reaction kinetics. Abstract: Exploring high-activity and durable 3d transition metal electrocatalyst for oxygen evolution reaction (OER) is one of the key issues in the water splitting reaction. Herein, a series of copper-based alloy (CuM, M = Fe, Co, Ni; FeCo, FeNi, CoNi; FeCoNi) nanoparticles have been synthesized by a rapid microwave-assisted solution phase method. Electrochemical measurements show that the catalysts possess outstanding OER activity as well as excellent long-term durability in alkaline electrolyte. The optimized samples of FeCoCu and FeCoNiCu exhibit superior activity with low overpotentials (265 and 269 mV at 10 mA cm -2 ), small Tafel slopes (49 and 48.9 mV dec -1 ), and low loss of activity after a 24 h stability test, which are much better than that of commercial RuO2 . The significant OER activity and stability are mainly attributed to the synergistic effect of multiple metal elements. The alloying strategy promotes the combination of the highly active iron, cobalt and nickel elements with the excellent conductive copper element, which not only changes the electronic structure of the material surface, but also accelerates the electron transfer and provides more active sites, thereby improving the electrocatalytic performance of the material. This work demonstrates an efficient and rapid method to prepare low cost electrocatalysts, which is important for the applications in energy conversion devices. Graphical abstract: Image, graphical abstract